DEGREES AND CLINICAL DESCRIPTION OF MENTAL RETARDATION - Kahramonova Zebuniso Raufjonovna (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  This  article  provides  information  on  the  degrees  and  clinical description  of  dementia.  Mentally  retarded  refers  to  a  steady  decline  in  mental, primarily intellectual development as a result of organic damage to the brain.